2017
DOI: 10.3168/jds.2016-12369
|View full text |Cite
|
Sign up to set email alerts
|

Effect of conjugated linoleic acid and acetate on milk fat synthesis and adipose lipogenesis in lactating dairy cows

Abstract: During biohydrogenation-induced milk fat depression (MFD), nutrients are spared from milk fat synthesis and are available for other metabolic uses. Acetate is the major carbon source spared and it may increase lipid synthesis in adipose tissue during MFD. The objective of this study was to compare the effect of trans-10,cis-12 conjugated linoleic acid (CLA) and the amount of acetate spared during CLA-induced MFD on adipose tissue lipogenesis. Nine multiparous, lactating, ruminally cannulated Holstein cows (244… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 67 publications
2
25
1
1
Order By: Relevance
“…For ruminant, the acetic acid is the main precursor for de novo synthesis of fatty acid in mammary gland, and provides the majority of the carbon. The milk fat yield was increased by 20% when the acetate was ruminal infused to lactating dairy cows, and the de novo synthesized fatty acids and palmitic acid were also increased in milk [16]. In this study, however, the milk fat was not affected by the acetic acid that tended to be decreased [8].…”
Section: Discussioncontrasting
confidence: 58%
“…For ruminant, the acetic acid is the main precursor for de novo synthesis of fatty acid in mammary gland, and provides the majority of the carbon. The milk fat yield was increased by 20% when the acetate was ruminal infused to lactating dairy cows, and the de novo synthesized fatty acids and palmitic acid were also increased in milk [16]. In this study, however, the milk fat was not affected by the acetic acid that tended to be decreased [8].…”
Section: Discussioncontrasting
confidence: 58%
“…This is likely associated with repartitioning of energy toward body fat reserves. Recently, Urrutia and Harvatine (2017) observed reduced lipogenic capacity of adipose tissue explants without changes in gene expression of key lipogenic enzymes during 4 d of trans-10,cis-12 C18:2 infusion. In our study, we did not detect levels of trans-10,cis-12 C18:2 in milk fat of most of our samples, but it is important to consider that other FA produced as intermediates in rumen biohydrogenation have been shown to reduce milk fat (Bauman et al, 2011) and potentially may be involved with energy partitioning.…”
mentioning
confidence: 99%
“…Baumgart et al [42] indicated that abomasal infusion of 3.5, 7, and 14 g/d of trans-10,cis-12 CLA in cows for five days decreased milk fat concentration by 24%, 37%, and 46%, respectively, while both isomers trans-10,cis-12 and cis-9,trans-11 CLA decreased milk fat concentration by 28%, 40.8%, and 38.6%-58.1%, respectively, in the studies by Urrutia and Harvatine [20], Vyas et al [43], and Haubold et al [7]. In the experiment by Dohme-Meier and Bee [44], the supplementation of unprotected CLA decreased fat content in cow milk by 53.8%.…”
Section: Fat Contentmentioning
confidence: 81%
“…Fish oil is more effective than plant oils for enhancing milk fat CLA content [16,17] and these responses can be further increased when fish oil is fed in combination with supplements rich in linoleic acid (LA) or CLA [18,19]. In the case of commercial preparations containing synthetically or microbiologically produced CLA [6,20], high prices limit their widespread use.…”
Section: Introductionmentioning
confidence: 99%